Pengaruh Pengetahuan dan Motivasi Ibu Rumah Tangga Tentang Gerakan Masyarakat Hidup Sehat (GERMAS) di Kelurahan Talang Bakung Kota Jambi - Nurfitriani Nurfitriani; Ersa Anggraini (Universitas Batanghari Jambi, 2019)
Lifesty and unhealthy behavior can cause health problems such as hypertension, stroke and coronary heart disease. This is the background of the government launching the Movement for Healthy Living Society (Germas) which focuses on doing physical activities, consumption of vegetables and fruit, and regular health checks. The purpose of this study was to determine the effect of housewife knowledge about the Healthy Living Ccomunity Movement (GERMAS) in the prevention hypertension in Talang Bakung sub-district year 2018. This research was a quantitative descriptive study with only. pre-test and post-test design experiment test design with one group intervention only. The population of 2,210 KK, with total sample as 20 IRT, age 21-59 years using purposive sampling technique. This research was carried out in August 2018 in Talang Bakung sub-District. study used a questionnaire, analyzed by paired t-test.The results showed the value of average knowledge before a given health education (pre test) dansetelah penkes 4.3 (post test) to 7.6. The value of average motivation before penkes (pre test) 23.55 and after penkes be 29.05. There is asignificant effect towards the knowledge and motivation of housewives about healthy living Society Movement (Germas) in hypertension prevention efforts with a p-value of 0.000. Expected role of health workers and cadres constantly improved again in providing counselling, information and education (KIE) in the form of a poster, or with leafleat outreach directly at housewives around the region binaanya with civic activities follow such as meng arisan, recitation and others so that the knowledge and motivation of housewives can be increased and conscious of the importance of maintaining healthy life patterns by living healthy Communities movement activities on a regular basis.